Effects of Moderate-Intensity Walking Exercise on Sleep Quality and Cardiopulmonary Capacity in Sedentary Adolescents and Young Adults: A Systematic Review: Walking Exercise Berintensitas Sedang pada Kualitas Tidur dan Kapasitas Kardiopulmoner Remaja dan Dewasa Muda Sedentary: A Systematic Review - Dewi, Kartika Arta; Fuadi, Dela Fariha (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Sedentary lifestyle is increasingly prevalent among adolescents and young adults and is associated with metabolic dysfunction, autonomic imbalance, reduced cardiovascular efficiency, and poor sleep quality. Specific Background: Moderate-intensity walking exercise is recognized as a simple aerobic activity that can be easily implemented to support physiological regulation and fitness. Knowledge Gap: However, empirical evidence synthesizing the effects of walking exercise simultaneously on sleep quality and cardiopulmonary capacity in sedentary youth remains limited. Aims: This study aims to systematically synthesize evidence on moderate-intensity walking exercise, including brisk walking, in improving sleep quality and cardiopulmonary capacity among adolescents and young adults with sedentary lifestyles. Results: Based on eight selected studies following PRISMA 2020 guidelines, walking exercise improved sleep quality components such as sleep duration and daytime function, although changes in global PSQI scores were not consistently significant, while cardiopulmonary capacity showed consistent improvement indicated by increased VO₂max/VO₂peak and decreased resting heart rate. Novelty: This study integrates dual outcomes of sleep quality and cardiopulmonary capacity within a single intervention framework focused specifically on sedentary adolescents and young adults, emphasizing intervention characteristics such as duration, intensity, and frequency. Implications: These findings support walking exercise as a practical, accessible, and evidence-based physical activity strategy for promoting cardiopulmonary health and supporting sleep regulation in sedentary populations. Highlights• Moderate walking programs increased sleep duration and daytime functioning• Aerobic capacity gains observed through VO₂max and heart rate changes• Structured interventions show consistent physiological adaptations KeywordsWalking Exercise; Sleep Quality; Cardiopulmonary Capacity; Sedentary Lifestyle; Adolescents